Predictors of the frequency of Australian children's consumption of unhealthy foods - Pettigrew, S.; Jongenelis, Michelle; Chapman, K.; Miller, C. (2015)
Background Child obesity interventions need to be based on a sound understanding of the factors that influence children's diets. Objective To investigate the relationship between a range of predictor variables and the frequency with which Australian children consume energy-dense, nutrient-poor (EDNP) foods. Methods A web panel provider was used to access 1302 parents of Australian children aged 8–14 years who responded to an online survey about their children's diets. Structural equation modelling was conducted to test a model of the factors contributing to the frequency of children's unhealthy food consumption. Results Of the tested variables, consumption of EDNP foods was primarily influenced by parents’ attitudes to these foods, children's pestering behaviours and perceived social norms relating to children's consumption of these products. Both pestering and social norms had significant direct effects on consumption frequency as well as indirect effects via their impact on parents’ attitudes to EDNP foods. Conclusion Environmental factors that contribute to both pestering and social norms are likely to be critical considerations in the development of child obesity interventions.